Manusia, Ilmu Pengetahuan dan Kesadaran Diri - Emanuel Prasetyono (Jurnal Orientasi Baru, 2013)
Human consciousness has brought about change and human development. The Enlightenment gave birth to a new generation of men and women who are aware of their human potentials to grow. Human mind is its centre. Yet, later science and technology have been its predominant influence. Modern culture has not been spared from this hegemony. The Enlightenments project therefore could be considered a failure particularly for conditioning as well as subjecting human understanding into what it merely empirical. The empirical is viewed as the only measure that counts. Does human being not deserve a more integral and holistic approach and understanding in every stage of its development? Human beings are personal, rational as well as relational. These are constitutive in their nature as they live in a community, in their dignity as a person and in the formation of human culture and civilization.